Intercostal neuralgia as a symptom of an osteoblastoma in thoracic spine. (2nd July 2015) - Kobayashi, Hiroshi; Shinoda, Yusuke; Ohki, Takahiro; Kawano, Hirotaka
Abstract : An osteoblastoma is a benign bone lesion most commonly affecting the spine; it is frequently found in the posterior elements of the vertebra. When an osteoblastoma originates in the spine, it usually causes dull and localised dorsal pain, but the period between symptom development and diagnosis can be long. MRI shows intense peritumoural oedema accompanying the osteoblastoma. We present a case of a 15-year-old boy with osteoblastoma at the level of the T8–9 left laminae causing intercostal neuralgia without direct invasion to the intercostal nerve. Immediately after surgery, intercostal neuralgia was diminished. To our knowledge, this is the first case of an osteoblastoma with intercostal neuralgia, which is possibly the key symptom for diagnosing an osteoblastoma in the thoracic spine.